Chicken feather rachis: An improvement over feather fiber derived electrocatalyst for oxygen electroreduction - Tyagi A.; Yadav A.; Sinha P.; Singh S.; Paik P.; Kar K.K. (My University, 2025)
Heteroatom doped carbon structures are widely recognized as efficient catalysts for oxygen reduction reaction (ORR). Herein, chicken feather rachis (FR), a poultry industry biowaste is explored as a novel precursor for ORR catalysis. This study comprises the effect of pyrolysis temperature on the structural characteristics and electrocatalytic performance of prepared electrocatalysts. N-doped carbon (NC) synthesized at 950 °C is further activated using KOH, ZnCl2, and H3PO4 at different temperatures. Poultry feather fiber (FF) derived samples were also prepared for comparison. KOH activated NCA-900 (NCA-K-900) exhibits the superior electrochemical performance in terms of onset potential (−0.02 V vs Ag/AgCl) in comparison to similar catalysts previously reported and prepared from feather fiber, which exhibits ~ −0.2 V vs Ag/AgCl. This is attributed to the mesoporous structure and increased ORR active C–N sites in FR derived samples as confirmed by adsorption isotherm and XPS analysis, respectively. In addition, it shows 96% current stability in chronoamperometric measurements for 15 h. It is better than the previously reported electrocatalyst prepared from coconut shell (90%, 13 h) and egg yolk (91%, 9 h) respectively. Hence, this study presents an improved environment friendly substitute for ORR catalysis. © 2019 Elsevier B.V.